Analysis of Papua Separatist Group Insurgency and the Indonesian Government's Contra-Insurgency from an International Law Perspective - Zulfikar Fabri; Djayeng Tirto; Puguh Santoso (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Rebellion or insurgency is one possible threat that interferes with the sovereignty and security of a country; the insurgency is come by the presence of non-state actors against state actors with the use source Power political and military with objective take over state power. The Papuan conflict began from marginal dissatisfaction and poverty, giving rise to a passion for liberation self, with do attacks, rebellions, and killings committed by the now OPM Free Papua Organization labeled as Papuan Terrorist Separatist Group KSTP. Therefore, it is essential to analyze descriptive qualitative To use study Insurgency and cons Insurgency from an international law perspective. According to International Law, The OPM status mentioned as Group Separatist Papuan terrorists (KSTP) are not as organization or Beligerent. Therefore, the government so far labeled the group as an insurgent. Based on Policy in progress conflict Papua terrorists who have differences in application, the Indonesian government has carried out effort Soft Power, Hard Power, and Smart Power strategies. As for the shape can form Cold counter-insurgency and hot counter-insurgency. Every effort settlement conflict insurgency must customize with conditions and form their respective territories. Keywords: Insurjency, Papuan Terrorist Separatist Group, International Law